2016
DOI: 10.1165/rcmb.2014-0486oc
|View full text |Cite
|
Sign up to set email alerts
|

Impaired E Prostanoid2 Expression and Resistance to Prostaglandin E2 in Nasal Polyp Fibroblasts from Subjects with Aspirin-Exacerbated Respiratory Disease

Abstract: Recurrent, rapidly growing nasal polyps are hallmarks of aspirin-exacerbated respiratory disease (AERD), although the mechanisms of polyp growth have not been identified. Fibroblasts are intimately involved in tissue remodeling, and the growth of fibroblasts is suppressed by prostaglandin E 2 (PGE 2 ), which elicits antiproliferative effects mediated through the E prostanoid (EP) 2 receptor. We now report that cultured fibroblasts from the nasal polyps of subjects with AERD resist this antiproliferative effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 20 publications
1
47
0
1
Order By: Relevance
“…For instance, B-cell differentiation can be altered by specific DNA demethylation patterns of gene segments that have been associated with the binding sites of B-cell-specific transcription factors, such as early B-cell factor 1, paired box 5, and E2F [48]. A recent article by Cahill et al [49] highlights the importance of epigenetic modifications in the pathogenesis of a subphenotype of aspirin exacerbated respiratory disease (AERD). The authors show that nasal polyp fibroblasts from patients with AERD are resistant to the anti-proliferative effects of prostaglandin E 2 (PGE 2 ).…”
Section: Five-year Viewmentioning
confidence: 99%
“…For instance, B-cell differentiation can be altered by specific DNA demethylation patterns of gene segments that have been associated with the binding sites of B-cell-specific transcription factors, such as early B-cell factor 1, paired box 5, and E2F [48]. A recent article by Cahill et al [49] highlights the importance of epigenetic modifications in the pathogenesis of a subphenotype of aspirin exacerbated respiratory disease (AERD). The authors show that nasal polyp fibroblasts from patients with AERD are resistant to the anti-proliferative effects of prostaglandin E 2 (PGE 2 ).…”
Section: Five-year Viewmentioning
confidence: 99%
“…The role of epigenetic targeting of PGE 2 pathway genes involved in the expansion of nasal polyps in AERD patients was recently investigated 80 . Fibroblasts, which are the major effector cells for airway remodeling, express the arachidonic acid pathway genes that are upregulated in AERD, and stimulation of the EP 2 receptor by PGE 2 represses the activation and growth of these cells.…”
Section: Epigenetics Of Aerdmentioning
confidence: 99%
“…In addition, fibroblasts from nasal polyps of patients with AERD have intrinsically lower expression of COX-2, PGE 2 and EP 2 receptor protein vs. aspirin-tolerant (AT) control subjects 81 . Cahill et al hypothesized that an intrinsic defect in EP 2 expression in nasal polyp fibroblasts, potentially a result of epigenetic modification at this locus, underlies the aggressive expansion and proliferation of nasal polyps in AERD patients 80 . To investigate this, the authors first isolated and cultured fibroblasts from nasal polyps of 18 patients with AERD and nine aspirin-tolerant patients with chronic rhinosinusitis and nasal polyposis, and nasal tissue from eight non-asthmatic controls undergoing surgery for concha bullosa 80 .…”
Section: Epigenetics Of Aerdmentioning
confidence: 99%
See 1 more Smart Citation
“…15 A very recent report demonstrated that ILC2s are recruited to the nasal mucosa during COX-1 inhibitor reactions in patients with AERD, and multiple studies have shown that eosinophilic nasal polyps are enriched with ILC2s. 1,16 Interestingly, some patients with AERD have shown PGE 2 hyporesponsiveness in granulocytes and polyp fibroblasts, 17,18 and if ILC2s in patients with AERD are also resistant to PGE 2 , then perhaps this is one mechanism by which persistent ILC2 activation could contribute to disease. As with the entire ILC2 field, we are witnessing a rapidly emerging and exciting window into novel mechanisms of allergic diseases.…”
mentioning
confidence: 99%